Corporate social responsibility in the Icelandic food retail sector : the significance of customer perspective in CSR strategy formation & a relationship between CSR & customer loyalty - Hanna Ragnheiður Ingadóttir 1987- (2016)
When businesses engage in socially responsible activities, it often encourages a positive corporate image which can result in increased customer loyalty. Food retail stores are among businesses that are progressively adopting corporate social responsibility (CSR) strategies into their operations, however no research has been conducted on CSR in the Icelandic food retail sector. In addition to contributing to this gap in research, the aim of this thesis is to find an effective way to successfully implement CSR in food retail stores, and research whether CSR affects customer loyalty in this customer-driven industry. Literature review revealed that it is important to research customer perspective when trying to find out how best to form and implement CSR. Thus, the research conducted was twofold, each quantitative. A CSR status evaluation in the form of a survey was conducted among managers of an Icelandic food retail brand, to see where the food retail stores currently stood on this matter. Furthermore, a customer survey was administered to 1403 participants, to research the importance customers of food retail stores place on different CSR factors, compared to the food retail brand´s CSR status. The study also examined whether CSR affects customer loyalty in the food retail industry. The key findings were that to customers of Icelandic food retail stores, the stakeholder factor is of highest importance when it comes to CSR. Also, a relationship between loyalty and CSR was analysed and a small, but positive correlation was discovered on a significant level between the two variables, indicating that CSR does affect customer loyalty in the food retail industry. The main value this research adds to the field of CSR literature are the important steps identified, that food retail stores should take, before implementing a long-term CSR strategy in their stores, as well as during implementation, in order for the strategy to be successful. Keywords: Corporate social responsibility, customer loyalty, Iceland, food retail ...